2022
DOI: 10.3390/agronomy12061413
|View full text |Cite
|
Sign up to set email alerts
|

Calcined Oyster Shell-Humic Complex as Soil Amendment to Remediate Cd- and As-Contaminated Soil

Abstract: Soil acidification in the subtropical region reduces soil productivity and increases the bioavailability of heavy metal(loid)s in soil. Here 800 °C-calcined oyster shell and leonardite-derived humic substance were combined to form a Ca-humic complex to remediate an acidic soil contaminated by cadmium (Cd) and arsenic (As) for safe vegetable production. In the pot experiment, the complex was added to soil as a soil amendment at 0%, 0.5%, 1.0%, 2.0%, and 5.0%. A 2.0% dose reduced Cd and As contents of the vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These results could be attributed to Cu resorption in the soil, Cu complexation with pepsin, or chemical precipitation of metals caused by the higher pH environment of the intestinal compartment [31]. The reducing agent's complexation with Cu makes them less soluble in the simulated gastric and intestinal environment [45]. Moreover, Cu had a higher bioaccessibility in the gastric compartment than in the intestinal one, mainly because the former had a much lower pH than the latter.…”
Section: Changes In Cu Plant Availability and Bioaccessibility After ...mentioning
confidence: 99%
“…These results could be attributed to Cu resorption in the soil, Cu complexation with pepsin, or chemical precipitation of metals caused by the higher pH environment of the intestinal compartment [31]. The reducing agent's complexation with Cu makes them less soluble in the simulated gastric and intestinal environment [45]. Moreover, Cu had a higher bioaccessibility in the gastric compartment than in the intestinal one, mainly because the former had a much lower pH than the latter.…”
Section: Changes In Cu Plant Availability and Bioaccessibility After ...mentioning
confidence: 99%
“…In "Calcined Oyster Shell-Humic Complex as Soil Amendment to Remediate Cd-and As-Contaminated Soil" by G. Yuan, D. Bi, J. Wei, and L. Xiao, a Ca-humic complex from leonardite-derived humic substances was prepared and employed as a soil amendment to remediate an acidic soil contaminated with Cd and As for the production of consumptionsafe vegetables [2]. Pot experiments with bok choy vegetables demonstrated that the Ca-humic complex decreased the Cd and As contents in the plant by 98% and 71%, respectively, and lowered the soil Cd and As bio-accessibility in simulated gastric and intestinal compartments, reducing health risks for humans.…”
mentioning
confidence: 99%